2022
DOI: 10.7150/jca.62433
|View full text |Cite
|
Sign up to set email alerts
|

Low expression of FOXP2 predicts poor survival and targets caspase-1 to inhibit cell pyroptosis in colorectal cancer

Abstract: Background: Colorectal cancer (CRC) is the third most common cancer worldwide. Several studies have suggested that FOXP2 functions as a tumour suppressor. However, to date, it remains unclear how FOXP2 influences CRC occurrence. Methods: We took advantage of CRC tissue samples and compared the expression of FOXP2 via immunohistochemistry assays. We elucidated the underlying function of FOXP2 in CRC cells by constructing a cell model with FOXP2 depletion. Co-IP experiments and immunofluorescence (IF) assays wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…For instance, FOXP2 epigenetically activates RPS6KA6 to enhance tumor cell apoptosis in thyroid cancer (31). FOXP2 interacts with caspase-1 to drive tumor cell pyroptosis in colorectal cancer (23). In the present study, FOXP2 blocked TGFβ signaling, which plays a key role in the pathogenesis of cancers.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…For instance, FOXP2 epigenetically activates RPS6KA6 to enhance tumor cell apoptosis in thyroid cancer (31). FOXP2 interacts with caspase-1 to drive tumor cell pyroptosis in colorectal cancer (23). In the present study, FOXP2 blocked TGFβ signaling, which plays a key role in the pathogenesis of cancers.…”
Section: Discussionmentioning
confidence: 47%
“…TGFβ/SMAD is involved in the carcinogenesis of lung cancer (23)(24)(25). FOXP2 overexpression suppresses tumor aggressiveness.…”
Section: Foxp2 Blocks Tgfβ/smad Signaling In Lung Cancermentioning
confidence: 99%
“…Mechanistic studies have shown that FOXP2 interacts with caspase‐1 and promotes its expression. [ 198 ] Metformin can inhibit tumor progression by inducing pyroptosis in ESCC by targeting the miR‐497/Proline‐, glutamic acid‐ and leucine‐rich protein 1 (PELP1) axis. [ 199 ] Photodynamic therapy can treat ESCC by inducing GSDME‐mediated pyroptosis, and PDT can activate caspase‐8 and caspase‐3 via Pyruvate kinase Pyruvate kinase (PKM2) to ultimately release GSDME‐N and trigger pyroptosis in ESCC cells.…”
Section: Pyroptosis In Gi Cancersmentioning
confidence: 99%
“…Pyroptosis, a new form of programmed cell death, leads to cleavage of gasdermin D (GSDMD) and activates inflammatory factors [4,5]. Substantial evidence suggests that pyroptosis plays a critical role in immune response and tumor progression, including CRC [6][7][8]. Long-term chronic pyroptosis of cancer cells triggered by the tumor microenvironment (TME) is more likely to promote cancer progression [9].…”
Section: Introductionmentioning
confidence: 99%